Pemberdayaan UMKM Tepung Mocaf Melalui Inovasi Produk Lokal dan Penerapan Digital Marketing - Awa, Awa; Rimadini, Amalia; Mulyadi, Musa; Rifky Ramadhan, Muhamad; Kurniawan Dwitama, Kiki; Nurastri Mustika, Siti Juwita; Yuningsih, Erni (Al-Khidmah Jurnal Pengabdian Masyarakat, 2024)
Sukabumi Regency is known as an agricultural producer, including cassava, which is the main commodity in Pasirdoton Village, Cidahu District. This village utilizes local wisdom in the agricultural sector to develop Mocaf Flour MSMEs. To increase competitiveness, sales results, and market share, empowerment and development of cassava flour-based products are very important. The Community Service (PkM) Team of Djuanda University applied observation, interview, socialization, and implementation methods to introduce derivative products such as Mocaf Noodles and Mocaf Cookies. The results showed a significant increase in brand awareness through social media and e-commerce, as well as an increase in sales with positive reviews from consumers. This program succeeded in introducing product innovation, expanding market access, and strengthening the brand identity of Mocaf Flour MSMEs, which are expected to survive and develop in the long term through the application of technology and digital marketing strategies.